2019
DOI: 10.3390/ijerph17010151
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing Gaps in the Development of Palliative and End-of-Life Care: A Qualitative Exploratory Study

Abstract: A global report found that the quality of dying in Hong Kong lagged behind that of other high-income economies. This study aims to examine the service gaps by conducting a qualitative exploratory study from multiple stakeholders’ perspectives. Purposive and snowball sampling strategies were used to maximize variation in the sample. We interviewed 131 participants, including patients, family members, health care providers, administrators, lawyers, and policy makers. The situation analysis helped identify the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 14 publications
3
25
0
Order By: Relevance
“…Fong et al 5 conducted a survey on speech therapists about palliative care and report that relevant practice guidelines and training are lacking, resulting in inconsistencies in practice and concerns about legal liability. The authors' findings are consistent with those of Chan et al, 6 who found that the overall development of EOL care is influenced by various factors at individual, organisational, legal, and sociocultural levels. Therefore, the recent public consultation is an opportune time for the government to overhaul development of EOL care in terms of policy, legislation, financial support, manpower planning, capacity building, and public education.…”
supporting
confidence: 90%
“…Fong et al 5 conducted a survey on speech therapists about palliative care and report that relevant practice guidelines and training are lacking, resulting in inconsistencies in practice and concerns about legal liability. The authors' findings are consistent with those of Chan et al, 6 who found that the overall development of EOL care is influenced by various factors at individual, organisational, legal, and sociocultural levels. Therefore, the recent public consultation is an opportune time for the government to overhaul development of EOL care in terms of policy, legislation, financial support, manpower planning, capacity building, and public education.…”
supporting
confidence: 90%
“…The results of a qualitative research 18 revealed that professionals working in the pre-hospital service were concerned with the patient's manifestations of will, but there was a possibility of contradicting the objectives of the service they perform. They also expressed a feeling of helplessness regarding the will of the family in relation to the Non-Resuscitation Order (NRO), and confessed that there was distrust in accepting the manifestations contained in the document even seeing the signature of the patient's physician.…”
Section: Discussionmentioning
confidence: 99%
“…(3,11) Given this consensus among healthcare professional regardless of the training experience and clinical background, training using an inclusive approach to enhance their preparedness would be the cornerstone of system-wide ACP implementation. (12) Study strengths and limitations This paper addresses the knowledge gap about the association between training and healthcare professionals' attitudes toward ACP. Although the survey included respondents with a wide range of clinical backgrounds, we acknowledged several study limitations when interpreting the study ndings.…”
Section: Discussionmentioning
confidence: 99%